Standardized Polyalthia longifolia leaf extract (PLME) inhibits cell proliferation and promotes apoptosis: The anti-cancer study with various microscopy methods - Vijayarathna, S.; Chen, Y.; Kanwar, J.R.; Sasidharan, S. (Elsevier, 2017)
Over the years a number of microscopy methods have been developed to assess the changes in cells. Some non-invasive techniques such as holographic digital microscopy (HDM), which although does not destroy the cells, but helps to monitor the events that leads to initiation of apoptotic cell death. In this study, the apoptogenic property and the cytotoxic effect of P. longifolia leaf methanolic extract (PLME) against the human cervical carcinoma cells (HeLa) was studied using light microscope (LM), holographic digital microscopy (HDM), scanning electron microscope (SEM) and transmission electron microscope (TEM). The average IC50 value of PLME against HeLa cells obtained by MTT and CyQuant assay was 22.00 mu g/mL at 24 h. However, noncancerous Vero cells tested with PLME exhibited no cytotoxicity with the IC50 value of 51.07 mu g/mL at 24 h by using MTT assay. Cytological observations showed nuclear condensation, cell shrinkage, multinucleation, abnormalities of mitochondrial cristae, membrane blebbing, disappearance of microvilli and filopodia, narrowing of lamellipodia, holes, formation of numerous smaller vacuoles, cytoplasmic extrusions and formation of apoptotic bodies as confirmed collectively by HDM, LM, SEM and TEM. In conclusion, PLME was able to produce distinctive morphological features of HeLa cell death that corresponds to apoptosis.